Extrahepatic alveolar echinococcus on multi-slice computed tomography and magnetic resonance imaging - Hui Guo (Nature Portfolio, 2021)
Abstract Alveolar echinococcus (AE) is a severe health problem in endemic areas. In recent years, the incidence of this disease in China has been increasing. The study was designed to illustrate the multi-slice computed tomography (MSCT) and magnetic resonance imaging (MRI) features of extrahepatic AE. A cohort of 33 patients who suffered from extrahepatic AE was enrolled consecutively from January 2012 to December 2017. The MSCT and MRI features of extrahepatic AE were recorded and analyzed by experienced radiologists. All cases secondary to hepatic AE, except two primary extrahepatic AE, were found in this study. Locations of extrahepatic AE included 19 (57.6%) lung, 10 (30.3%) adrenal gland, 9 (27.3%) brain, 5 (15.2%) peritoneal cavity, 5 (15.2%) spleen, 4 (12.1%) diaphragm, 3 (9.1%) kidney, 3 (9.1%) retroperitoneal, and 2 (6.1%) vertebra; Involvement of 1 (3.0%) heart, 1 (3.0%) mediastinum, 1 (3.0%) muscle, and 1 (3.0%) pancreas was rare. AE of the lung usually appeared as irregular and scattered nodules with small vacuoles or cavities inside and peripheral distribution. Multiple cerebral nodules with calcification and surrounding edema were the most common features seen in brain AE. Adrenal gland AE presented as plaques containing different sizes of hypodense areas and different amounts of calcification. Injection of contrast medium showed no enhancement of lesions except in the brain. MSCT and MRI are reliable imaging methods for the diagnosis of extrahepatic AE. When one AE patient is clinically confirmed, MSCT scan from the chest to the abdomen should be performed to exclude other organs AE.